Assessment of the Rock Slopes by Kinematic and Limit Equilibrium Methods on the Bağlarbaşı - Tekke (Gümüşhane) Motorway - Selçuk Alemdağ; Zülfü Gürocak; Ceren Özkirişçi Oktay (Doğal Afetler ve Çevre Dergisi)
Kinematic analysis method is one of the widely used methods to evaluate potential failures such as planar, wedge and toppling in rock slopes. In this method, orientations of slope and discontinuity with the friction angle of the discontinuities planes are used to analyze possible failure types. However, the reliability of the results obtained from kinematical analyses is not sufficient for optimum slope design. For this reason, it is necessary that the results of kinematical analyses should be controlled using limit equilibrium or numerical analyses. In this study, stability of rock slopes on the highway of Bağlarbaşı-Tekke (Gümüşhane) was investigated using kinematical and limit equilibrium analyses. The results of thekinematical analyses showed that there may be planar and wedge type instabilities for the rock slopes numbered 5, 6, and 7. The limit equilibrium analyses conducted for the types of plane and wedge show that the rock slopes numbered 5 and 6 are instable while number 7 is stable.